The national agrarian strike of 2013 and the agricultural policy 2006-2014 - Campos-Martínez, Froilán (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The general objective of this article was to analyze the conditions and  consequences of the 2013 national agrarian strike and the agricultural policy 2006-2014, through a diagnosis of the agricultural sector in Colombia, including the background (a look at economic policies, neoliberalism and economic liberalization in the country), current national situation, recently approved farmer rights, agricultural reality of the peasantry against human rights and analysis of jurisprudence.